To see or not to see: A study comparing four-way avatar, video, and audio conferencing for work - Junuzovic, Sasa; Inkpen, Kori; Sedlins, Mara; Fisher, Kristie; Tang, John (GROUP 2012, 2012)
We conducted a study comparing avatar conferencing with video and audio conferencing for work scenarios. We studied nine four-person teams using a within-subjects design that measured users' perceptions and preferences across the conferencing conditions. Video was rated highest in all measures. Avatar and Audio were rated similarly, except for sociability, where Avatar was rated higher than Audio, and realism, where Avatar was rated lower than Audio. While users appreciated how avatar conferencing brought them together in a common virtual space, they found the cartoon avatars to be inappropriate for a professional discussion. As a result, participants preferred Video the most and Avatar the least for a business meeting. Lower ratings for the avatar condition were partly due to users’ frustrations when the avatar system did not track them perfectly. When assuming a “perfect” system, preference for Avatar increased significantly while preference for Audio and Video remained unchanged.